Father involvement, father-child relationship, and attachment in the early years. Issue 1 (2nd January 2020) - Cabrera, Natasha J.
ABSTRACT: Over the last few decades fathers have become an increasing presence in research, yet research on fathers still lags behind that on mothers. In fact, most research on parents still includes the mother. Consequently, there is still much to learn about fathers. This is particularly true for understanding how parent-child relationship functioning in the early years can serve as a source of emotional security that promotes healthy development across developmental domains and across the lifespan. In this commentary, I take a social policy broad lens to highlight the empirical and theoretical connections among father- relationship, father involvement, and father-child attachment.